Protest on the Fly - Snow, David A.; Moss, Dana M. (American Sociological Review, 2014)
This article reexamines spontaneity as an important, albeit neglected, mechanism in collective action dynamics, and elaborates on its operation and effects in protest events and social movements. We do not presume that spontaneity is routinely at play in all collective actions. Rather, based on our grounded analysis of historical and ethnographic data, we contend that spontaneity is triggered by certain conditions: nonhierarchical organization; uncertain/ambiguous moments and events; behavioral/emotional priming; and certain ecological/spatial factors. We conclude by elaborating why the activation of spontaneous actions matters in shaping the course and character of protest events and movements, and we suggest that spontaneity be resuscitated in the study of collective action and everyday life more generally.